2011
DOI: 10.1007/s12630-011-9517-3
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of pulmonary edema with variable mechanical ventilation in a porcine model of acute lung injury

Abstract: Objective Resolution of the acute respiratory distress syndrome (ARDS) requires clearance of pulmonary edema. Biologically variable ventilation (BVV) strategies that improve gas exchange, lung mechanics, and inflammatory mediators in ARDS may be beneficial in this regard. We used quantitative computed tomography (CT), a single indicator thermodilution system (PiCCOÒ) to determine extravascular lung water (EVLW), and the change in edema protein concentration over time to compare edema clearance with BVV vs conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…In a porcine oleic acid model, total lung weight and density were reduced with variable controlled mechanical ventilation compared to conventional controlled mechanical ventilation and average alveolar fluid clearance rates were positive compared to negative [34]. However, analysis of corresponding wet:dry ratios of the post-mortem lung showed no effects of variable controlled mechanical ventilation compared to conventional controlled mechanical ventilation in five out of six investigations, independent of the injury model [13, 29-31, 34, 44].…”
Section: Inflammation and Damagementioning
confidence: 99%
See 2 more Smart Citations
“…In a porcine oleic acid model, total lung weight and density were reduced with variable controlled mechanical ventilation compared to conventional controlled mechanical ventilation and average alveolar fluid clearance rates were positive compared to negative [34]. However, analysis of corresponding wet:dry ratios of the post-mortem lung showed no effects of variable controlled mechanical ventilation compared to conventional controlled mechanical ventilation in five out of six investigations, independent of the injury model [13, 29-31, 34, 44].…”
Section: Inflammation and Damagementioning
confidence: 99%
“…Similarly, venous admixture was reduced in variable PSV but not in conventional PSV [16,36]. In a model of lung injury induced by oleic acid in pigs [13,14,34], variable controlled mechanical ventilation did not importantly influence the dead space, suggesting that shunt reduction is more prominent then reduction of dead space during variable ventilation.…”
Section: Ventilation-perfusion Matchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, variable ventilation also facilitates more uniform lung recruitment during acute lung injury. Using computed tomography in a porcine oleic acid-induced lung injury model, Graham et al 28,29 demonstrated significantly improved recruitment of nonaerated and poorly aerated lung areas without a concomitant increase in hyperaerated lung areas. In addition, there is evidence that the recruitment associated with variable ventilation is more sustained than that with monotonous controlled mechanical ventilation when used in conjunction with PEEP.…”
Section: Controlled Variable Ventilation and Ardsmentioning
confidence: 99%
“…[7][8][9] Novel ventilator modes, such as adaptive servo ventilation, demonstrate that application of variable support in one physiologic system (respiratory system) promotes variable physiology in a linked system (cardiac). 10 What can we conclude from the article by Bishop et al, which shows us that a vasoconstrictor alters the fractal dimension of the blood pressure (but not the heart rate) while atropine alters the fractal dimension of the heart rate (but not the blood pressure)?…”
mentioning
confidence: 99%